Variable structure controllers for unstable processes. (August 2015) - Ablay, Günyaz
Highlights: A variable structure controller is developed for unstable systems. Robust and high-performance responses are obtained. ITAE based optimal parameter tuning algorithm is provided. A direct auto-tuning method is developed. Existing control software and hardware can directly be used in applications. Abstract: A variable structure control (VSC) method for unstable industrial processes is proposed. The proposed control method is able to provide a highly satisfactory system performance and to tackle with robustness issues of the processes in the presence of uncertainties. An ITAE-based numerical tuning algorithm for acquiring optimal control parameters, and a direct auto-tuning mechanism for the proposed controller are also provided. The performance of the proposed VSC method is illustrated on some unstable process models including a continuous stirred tank reactor (CSTR), in order to show its effectiveness, validity and feasibility.